AUTOMATIC EXCHANGE OF INFORMATION SEBAGAI SARANA MENINGKATKAN EMPAT PILAR KEPATUHAN PAJAK - Supriyadi Supriyadi (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
The Government of Indonesia carr out extra efforts program to increase tax compliance and to explore potential tax revenues, one of which is through the use of Automatic Exchange of Information (AEoI). This aims of this study are to analyze the utilization of AEoI in order to increase tax compliance; to analyze AEoI to explore potential tax revenue; and to analyze the barrier of using AEoI in an effort to increase the four pillars of tax compliance. The four pillars of tax compliance include registration, payment, reporting and payment of tax arrears. This research is qualitative in nature by using the literature study method through combining several literature related to national and global implications of AEoI using secondary data. The entire data is collected by using data collection methods (library research). The results of the study indicate that the Directorate General of Taxes has not utilized the AEoI data to improve the four pillars of tax compliance. AEoI Data Management is still at the stage in the process of registration, reporting and change. The factors that inhibited the use of AEoI were that Directorat General of Taxes (DGT) was still in the process of preparing the operating standards and procedures for the use of AEoI and the establishment of a Directorate of Data and Information. Besides that, socialization to the vertical units of DGT and taxpayers is still limited.